Mechanically Robust Hydrogels Facilitating Bone Regeneration through Epigenetic Modulation. Issue 32 (25th September 2022) - Yu, Tingting; Zhang, Lingyun; Dou, Xueyu; Bai, Rushui; Wang, Hufei; Deng, Jie; Zhang, Yunfan; Sun, Qiannan; Li, Qian; Wang, Xing; Han, Bing
Abstract: Development of artificial biomaterials by mimicking extracellular matrix of bone tissue is a promising strategy for bone regeneration. Hydrogel has emerged as a type of viable substitute, but its inhomogeneous networks and weak mechanics greatly impede clinical applications. Here, a dual crosslinked gelling system is developed with tunable architectures and mechanics to promote osteogenic capacity. Polyhedral oligomeric silsesquioxane (POSS) is designated as a rigid core surrounded by six disulfide‐linked PEG shells and two 2‐ureido‐4[1H]‐pyrimidinone (UPy) groups. Thiol‐disulfide exchange is employed to fabricate chemical network because of the pH‐responsive "on/off" function. While self‐complementary UPy motif is capable of optimizing local microstructure to enhance mechanical properties. Taking the merits of biocompatibility and high‐mechanics in periodontal ligament stem cells (PDLSCs) proliferation, attachment, and osteogenesis, hybrid hydrogel exhibits outstanding osteogenic potential both in vitro and in vivo. Importantly, it is the first time that a key epigenetic regulator of ten‐eleven translocation 2 (Tet2) is discovered to significantly elevate the continuously active the WNT/ β ‐catenin through Tet2/HDAC1/E‐cadherin/ β ‐catenin signaling cascade, thereby promoting PDLSCs osteogenesis. This work represents a general strategy to design the hydrogels with customized networks and biomimetic mechanics, and illustrates underlying osteogenic mechanisms that will extend the design rationales for high‐functional biomaterials in tissue engineering. Abstract : A dual‐crosslinked gelling system with tunable architectures and mechanical properties can promote periodontal ligament stem cell‐mediated bone regeneration by activating WNT/ β ‐catenin through translocation 2 epigenetic regulation.